Radio Listeners Clubs (RLCs) in Rwanda Help Close Gender Gaps in Farmers’ Use of Climate Information - CGIAR Research Program on Climate Change, Agriculture and Food Security (2021)
Radio Listeners Clubs (RLCs) in Rwanda helped close gender gaps in smallholder farmers’ use of climate information. RLCs empowered women to make informed agricultural decisions and also contributed toward improved food security of smallholder households. 225 Farmer Promoters were trained to lead their village groups in weekly meetings to listen and discuss climate service radio programs, participate in live call-in shows, share and record their plans to act on what they learned, and share the information with others.